Communication Innovation and Lifelong Learning of the Elderly - musikanon, chutima (วารสารวิจัยมหาวิทยาลัยเวสเทิร์น มนุษยศาสตร์และสังคมศาสตร์, 2020)
Thailand is reaching the Aging Society like the other countries globally. When elderly people retire from work, they will encounter many changes like Physical changes, Psychological and emotional, and social changes. These changes can cause them many problems. They will feel lonely, melancholic as well as stressful, etc. To avoid these problems they will encounter, lifelong learning seems to be questioned together with the technological world. How could we utilize technology to lead to the happiness of them? According to the literature review, many countries emphasize more the elderly and attempt to find the best way for the elderly after retirement. It can be concluded that they include Thailand reach the same goals and try on applying communication innovation with lifelong learning methodology with the elderly.